Impact of Overweight on Effectiveness of Treatment with Human Growth Hormone in Growth Hormone Deficient Children: Analysis of German KIGS Data - Reinehr, T.; Bechtold-Dalla Pozza, S.; Bettendorf, M.; Doerr, H.-G.; Gohlke, B.; Hauffa, B. P.; Kaspers, S.; Land, C.; Mehls, O.; Schwab, K.-O.; Stahnke, N.; Ranke, M. B.; null (Experimental and Clinical Endocrinology & Diabetes, 2011)
We hypothesized that overweight children with growth hormone deficiency (GHD) demonstrate a lower response to growth hormone (GH) as a result of a misclassification since obesity is associated with lower GH peaks in stimulation tests.Anthropometric data, response, and responsiveness to GH in the first year of treatment were compared in 1.712 prepubertal children with GHD from the German KIGS database according to BMI (underweight=group A, normal weight=group B, overweight=group C) (median age: group A, B, C: 7.3, 7.28, and 8.4 years).Maximum GH levels to tests (median: group A, B, C: 5.8, 5.8, and 4.0 µg/ml) were significantly lower in group C. IGF-I SDS levels were not different between the groups. Growth velocity in the first year of GH treatment was significantly lower in the underweight cohort (median: group A, B, C: 8.2, 8.8, and 9.0 cm/yr), while the gain in height was not different between groups. The difference between observed and predicted growth velocity expressed as Studentized residuals was not significantly different between groups. Separating the 164 overweight children into obese children (BMI>97th centile; n=71) and moderate overweight children (BMI>90th to 97th centile, n=93) demonstrated no significant difference in any parameter.Overweight prepubertal children with idiopathic GHD demonstrated similar levels of responsiveness to GH treatment compared to normal weight children. Furthermore, the IGF-I levels were low in overweight children. Therefore, a misclassification of GHD in overweight prepubertal children within the KIGS database seems unlikely. The first year growth prediction models can be applied to overweight and obese GHD children.
Keywords: growth hormone deficiency; growth hormone treatment; obesity; prediction model; index of responsiveness